Environmental, Health, and Equity Co-benefits in Urban Climate Action Plans: A Descriptive Analysis for 27 C40 Member Cities - Johnson, Lauren; Krisko, Perrin; Malik, Maha; O'Donnell, Catherine; Pendleton, Nick; Ahn, Doyeon; Bizberg, Andrea; Chafe, Zoe A.; Kim, Daniel; McCormick, Sabrina; Naidoo, Seneca; Anenberg, Susan C. (Frontiers in Sustainable Cities, 2022)
Many actions to reduce greenhouse gases (GHGs) in cities have benefits for environmental quality, public health, and equity. These local and immediate “co-benefits” can include cleaner air, expanded green space, improved physical activity, and reduced noise. However, progress incorporating co-benefits assessments into climate mitigation planning has been limited. Here, we capitalized on the new availability of climate action plans (CAPs) from dozens of C40 cities to explore the stated role of environmental quality, health, and equity in urban GHG mitigation planning. Specifically, we qualitatively reviewed how four topics — equity, exposure to environmental risk factors, health effects of climate change, and health co-benefits of GHG mitigation — were addressed in CAPs from 27 C40 member cities. The cities span Africa, Asia, Australia, Europe, North America, and South America. We found that more references pertained to exposures (57% of all identified references across the four topics) than to equity (21%), health co-benefits of GHG mitigation (15%), or health effects of climate change (7%). On average across all cities, five exposure categories represented the majority of exposure references: green space (23% of total coded exposure references), disasters (20%), physical activity (24%), heat (16%), and air quality (12%). Approximately two-thirds of health effects and health co-benefits references noted a link with health generally, without specificity to disease or other health outcome. Our results indicate that while environmental quality is commonly considered in CAPs, health effects of climate change and health co-benefits of GHG mitigation are mentioned less frequently. Future work should further develop methods to qualitatively and quantitatively assess health consequences of action and inaction to reduce GHG emissions, using approaches that are appropriate for and accessible to multiple levels of governments.